PENERAPAN MODEL PROBLEM BASE LEARNING (PBL) DENGAN MEDIA VIDEO BERBASIS DIGITAL UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR DI KELAS V PADA MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN PECAHAN DI SD MARGORUKUN SURABAYA TAHUN PELAJARAN 2023/2024 - Wiwik Sukesi; Lina Listiana; Diah Eka Sulistyorini (PROCEEDING UMSURABAYA, 2024)
This study was conducted to determine the learning outcomes and understanding of the material on the addition and subtraction of fractions using the Problem Based Learning (PBL) model for fifth-grade students at SD MARGORUKUN Surabaya. The research method used is a pre-experimental design. The research subjects consisted of 16 students. The research instruments used were a test sheet with 10 questions, a lesson implementation sheet, student reflection, attitude observation sheet, and skills observation sheet. Data collection techniques were conducted through observation, tests, and questionnaires. Data analysis was performed based on the results of the implementation of the PBL model, skills sheets, and student response questionnaire data. The results of the lesson implementation had an average score of 98, categorized as excellent, with attitude results showing a score of 81. 8, pre-test knowledge score of 83. 6, post-test knowledge score of 95. 45, critical thinking skills through observation scored 96. 5, categorized as excellent, and communication skills scored 98. 8, categorized as excellent. The use of digital-based video learning media was highly effective in teaching mathematics, particularly the material on addition and subtraction of fractions. The conclusion of this study is that the PBL model can enhance students' skills in teamwork, critical thinking, motivation, and significantly improve their learning outcomes.